Gdje je nestao Winston Smith? - Mauro Dujmović ([sic])
1984 is a peculiar symbol of a tragic future of the mankind. Orwells intention, more or less all his critics agree on that, was not to predict but to warn and to prevent the destruction of the human personality. Political manipulation of reality through the control of the past and language lies in the centre of Orwell’s nightmare. Orwell’s fictional world and reality in which we live provide an answer to a common central question, the question of human freedom. Human existence and freedom have been inseparable since the beginning. Man is a victim of strong influences, which deepen an individual’s agony and his fear of everyday life in which he feels totally lost and alone like a drop in the ocean. Following the example of the main character Winston Smith it is evident that human nature is influenced by the structure of the modern society, that is the way in which social and political organisations, culture and mass media influence human nature. Therefore the question is how and in which ways has the modern man been conditioned and what is his real role within the modern society? This article has been inspired by the writings of some of the greatest contemporary minds who are fierce critics of the contemporary society and sincere fighters for human emancipation, the establishment of a human society and a well-rounded person, promotors of individual freedom and spontaneity, of free self-expression and constant improvement of love towards life.